Marketability of probiotics in the Philippines - Aguinaldo, Buenaventura E., II (Animo Repository, 2015)
This thesis described the attitudes of consumers on probiotics. Consumers are aware of probiotics. A regression analysis was used to show the results of marketing mix on consumer attitudes. The results showed that doctors, internet and news had an impact on consumer’s attitude on probiotics. A mean scores of 2.8 showed that consumers viewed that testimonial and anecdotal information alone on therapeutic effects of probiotics may constitute false and misleading advertisement. Also a mean score of 2.92 for doctors showed testimonial and anecdotal information alone on therapeutic effects of probiotics constitute false and misleading advertisement. In this study, 54% of respondent doctors do recommend the use of probiotics in their practice. The term label is not confined of the product label and also include matter that “supplements or explains” the attached label, even if it does not physically accompany the product.Third party literature constitutes labeling under the doctrine enunciated in Vitamin, 40 Cases and Sterling Vinegar. If it is labeling, under Kordel doctrine it is advertisements. If the labeling is under Vitamin, then Article 112 of RA 7394 applies. If the label is under 40 Cases, then Third Party Literature apply and Article 112 does not apply. If the label is under Sterling Vinegar, it would not constitute false and misleading advertising.